Penyelesaian Hukum Atas Kredit Macet Bank Melalui Panitia Piutang Negara (PUPN) - Malik Mahardika AR (Justicia Journal, 2012)
This study questioned What are some factors causing the rise of bad loans, both internally and externally and how the process of completion through PUPN. Through the method, normative with the processing of the data deductively. The results of this study found that the factors causing bad loans internally due to less careful in assessing the collateral; and or insensitivity in monitoring the credit, while the external factor arises because. poor management of the debtor's business, bad character debtor, and coercion and loan resolution melalul PUPN are: the handover of the management of state receivables, calls and warning calls, on-site inspection and safety assurance, interviews and News Events FAQ, the Joint Statement, Determination of Number of State Receivables , billing forced once by letter, foreclosure, disbursement of collateral, forced weight, Establishment of state receivables for Billable As yet, the establishment of state receivables paid off and finished.